2020
DOI: 10.1080/24749508.2020.1833629
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of models to estimate direct runoff volume from an agricultural watershed

Abstract: Generally, runoff records are the most important input data in water resource management; however, their availability is very limited especially in developing country as compared to rainfall records, especially under medium and small-scale catchments. In our study, we estimated runoff from ungauged agricultural watershed with the curve number method and empirical mathematical models were compared with SCS-CN. Empirical mathematical models (Inglis and De Souza Formula (IDS), Turc relationship (TR), Indian Irrig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The Department of Irrigation in India produced an empirical equation depending on data acquired from the Reihand River, which was used by Rawat et al (2021). Equation ( 8) represents the relationship between rainfall and runoff as follows:…”
Section: Coutagine Relationship (Cor)mentioning
confidence: 99%
See 1 more Smart Citation
“…The Department of Irrigation in India produced an empirical equation depending on data acquired from the Reihand River, which was used by Rawat et al (2021). Equation ( 8) represents the relationship between rainfall and runoff as follows:…”
Section: Coutagine Relationship (Cor)mentioning
confidence: 99%
“…This envisages the necessity of soft computing techniques for better prediction of the basin yield to achieve sustainable development of the watersheds. Rawat et al (2021) assessed annual runoff in an ungauged agricultural watershed using the SCS-CN and empirical mathematical methods. Results showed that the Inglis and DeSouza IDS model can simulate annual runoff as closely as the SCS-CN model and has the lowest RMSE value of 7.75, and the ranking of this model was ranked first compared with the other eight models.…”
Section: Introductionmentioning
confidence: 99%
“…The SCS-CN method, as developed by the US Department of Agriculture (USDA) Soil Conservation Service (SCS), primarily aimed at estimating rainfall excesses from rainfall [18]. The method has been readily accepted and used widely in numerous hydrologic studies to estimate surface runoff, such as for ungauged agricultural watersheds, quantifying vulnerability of soil erosion, and the studies monitoring spatio-temporal variability in LULC patterns [41,43,[52][53][54]. The SCS-CN method for the Indian conditions was used in the estimation of surface runoff from the IITB campus.…”
Section: Soil Conservation Services-curve Number (Scs-cn)mentioning
confidence: 99%